2021
DOI: 10.3390/ijerph182413080
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Cigarette Use among Adolescents and Young Adults in Austria from 2004–2020: Patterns of Change and Associations with Socioeconomic Variables

Abstract: Background: Adolescents and young adults are a crucial target group for preventing harm related to substance use. Recently, declining alcohol and tobacco consumption in young people has been observed in many countries. Based on survey data from 2004 to 2020, we describe time trends for several subgroups of adolescents and young adults (based on consumption levels and socioeconomic variables) and analyze associations between the level of alcohol per capita consumption or daily smoking and socioeconomic variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It was found that gender, school year, and academic performance were statistically significant predictors of drinking experience. Some studies have already reported that drinking behaviors were higher in male students [ 2 , 14 ]. This study found evidence consistent with this, possibly because female students had more positive attitudes than male students toward the early prevention of drinking or smoking [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that gender, school year, and academic performance were statistically significant predictors of drinking experience. Some studies have already reported that drinking behaviors were higher in male students [ 2 , 14 ]. This study found evidence consistent with this, possibly because female students had more positive attitudes than male students toward the early prevention of drinking or smoking [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Students from middle and lower economic statuses also had a high drinking rate, which was linked to the high prevalence of alcohol use disorder among Korean adults in the low-income group [ 18 ]. In contrast, some studies have reported that alcohol and tobacco consumption rank high among public health priorities for young adolescents in affluent countries [ 14 ]. The Korean economy is the world’s 10th largest in terms of scale and 18th largest in per capita income among the Organization for Economic Co-operation and Development (OECD) countries [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender differences in choosing a healthy lifestyle have been observed [1]. Women tend to be more sedentary than men with respect to following an active lifestyle [4]. They are also more likely to show greater adherence to a healthy dietary pattern [1].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption can lead to numerous health problems such as problems related to bone density, reproduction, and even fertility [ 6 , 7 ]. Tobacco use may also begin during this stage, as this substance acts as a facilitator of social interaction and is socially approved [ 8 , 9 ]; however, tobacco use has become a public health problem, as it is occurring earlier in young adolescents. The onset of alcohol and tobacco consumption may precede the consumption of substances such as cannabis, with numerous studies [ 10 , 11 , 12 ] affirming the effects of this substance on the brain, from a functional and structural point of view.…”
Section: Introductionmentioning
confidence: 99%